Umsetzung des Nationalen Aktionsplans zur nachhaltigen Anwendung von Pestiziden. Bestandsaufnahme zur Erhebung von Daten zur Belastung von Kleingewässern der Agrarlandschaft. - (:unkn) unknown (My University, 2017)
Mit dem Vorhaben "Umsetzung des Nationalen Aktionsplans zur nachhaltigen Anwendung von Pestiziden - Bestandsaufnahme zur Erhebung von Daten zur Belastung von Kleingewässern der Agrarlandschaft" sollen die Grundlagen für eine Verbesserung der Datenlage zum Belastungszustand der Kleingewässer der Agrarlandschaft mit Pflanzenschutzmitteln geschaffen werden. Hierzu wurde in den Bundesländern der Bestand an chemischen und biologischen Monitoringdaten zu kleinen Oberflächengewässern (Stand- und Fließgewässer) abgefragt. Ab 2016 soll ein Rahmenkonzept für ein zukünftiges, repräsentatives Monitoring abgestimmt sowie ein fachlich begründeter Vorschlag für einheitliche Kriterien für die Bewertung der Monitoringergebnisse erarbeitet werden. Dafür wurden in diesem Vorhaben u. a. Informationen zu vorhandenen Messprogrammen der Länder analysiert und Vorschläge für die Auswahl geeigneter Messstellen und -methoden sowie der einzuschließenden Substanzen entwickelt.

The project "Implementation of the National Action Plan on sustainable use of pesticides - survey on the state of data on the pollution of small water bodies in the agricultural landscape" aims at providing the basis for consolidation and improvement of the current available data on the level of pollution by plant protection products in small water bodies of the agricultural landscape. Thus, as the first step, chemical and biological monitoring data of small water bodies (standing and flowing water bodies) were requested from the German Länder. Subsequently, the data were assessed regarding their suitability to representatively describe the level of pollution in small water bodies of the agricultural landscape. As from the year 2016, a conceptual framework for a future representative monitoring will be coordinated, closely involving the Länder authorities. Moreover, a professionally justified proposal concerning harmonised criteria for the assessment of the monitoring will be developed. Therefore, for example, information about existing monitoring programmes of the Länder was analysed and recommendations for the selection of monitoring sites and methods as well as relevant substances were made in the project. With respect to the assessment criteria for the monitoring, the project needed to examine the possibility of using the SPEAR-index, which has been proposed by the National Action Plan, as an ecological pollution indicator. The results of the inventory and first cornerstones for a future monitoring concept were discussed with representatives of the Länder at a workshop on 6/7 October 2015 in Koblenz, Germany. The outcomes of the workshop will be considered for the conception of the follow-up project "Implementation of the National Action Plan on sustainable use of pesticides - development of a representative monitoring concept for assessment of the pollution of small water bodies in the agricultural landscape".
Keywords: Umweltschutz; Gewässerschutz; Landwirtschaft; Oberflächenwasser; Schadstoff; Risikoanalyse; Zulassung; Umweltverträglichkeit; Pestizid; Pflanzenschutzmittel; Datenanalyse; Gewässerökologie; Monitoring